Desenvolvimento e validação do osats para varicocelectomia microcirúrgica e de modelo ex-vivo não sacrificado de treinamento - Marcelo Esteves Chaves Campos (2019)
The aim of this study was (1) to perform a cross-cultural adaptation of the global rating scale of the Objective Structured Assessment of Technical Skill (OSATS) tool into BrazilianPortuguese language, and to determine its reproducibility and validity in Brazil, (2) to develop and test the validity of a new test of specific technical skill for microsurgical varicocelectomy and (3) to develop and test the validity of a novel simulated model of this procedure. The study consisted of three parts. Firstly, (1) a Brazilian-Portuguese version of global rating scale of OSATS was created through a process of translation, back-translation, expert panel evaluation, pilot testing and then its validation. After, (2) a task-specific checklist of microsurgical varicocelectomy was created and then validated. Lastly, (3) twelve human placentas were prepared and the microsurgical varicocelectomy simulation models were built. For the validation phase of the third part, we formed a group of three experts and a group of nine novices, who had to perform the steps of microsurgical varicocelectomy on a simulation model. Each participant was filmed and two blinded raters would then evaluate their performance using the Brazilian-Portuguese version of global rating scale of OSATS and the task-specific checklist of microsurgical varicocelectomy. Participants provided feedback through questionnaires. Both the OSATS assessments tools and the microsurgical varicocelectomy training model had the face, content and construct validities achieved. This preliminary study suggests that the global rating scale of OSATS and the task-specific checklist of microsurgical varicocelectomy can reliably and validly assess surgical skills. Human placenta simulation model may be a training tool for providers who are looking to learn the technique of microsurgical varicocelectomy or perfect their skills performing this operation.Key-Words: assessment, simulation, varicocelectomy, microsurgery, training